The impact of audit committee features on environmental and community disclosure – empirical evidence from GCC countries - Abdelmohsen Desoky (Investment Management & Financial Innovations, 2024)
This study examines the extent of environmental and community disclosures and evaluates how audit committee features influence such disclosures among listed firms in Bahrain and Kuwait, Gulf Cooperation Council (GCC) countries of emerging markets. The research employs an unweighted disclosure index comprising 18 items related to environmental and community disclosures, analyzing 432 firm-year observations across Bahrain and Kuwait covering a nine-year period (2015–2023). Three audit committee features (independence, number of meetings, and size) along with the number of other board committees are examined in this empirical investigation. Descriptive analysis indicates that the sampled firms offer 44.25% and 60.60% of environmental and community information, respectively, signaling a satisfactory disclosure level in Bahrain and Kuwait. This demonstrates progress compared to prior studies in GCC countries. Hierarchical Multiple Regression models demonstrate that all four models significantly describe the dependent variables. Regression model four exhibits the highest explanatory power in explaining community information. Audit committee independence and size emerge as determinants of community information, while only audit committee independence is associated with environmental information. The results of this study bear significant implications for governmental bodies and regulatory authorities aiming to strengthen disclosure regulations and promote corporate governance frameworks within GCC nations.